2012
DOI: 10.5194/angeo-30-613-2012
|View full text |Cite
|
Sign up to set email alerts
|

Equinoctial asymmetry in solar activity variations of <I>Nm</I>F2 and TEC

Abstract: Abstract. The ionosonde NmF2 data (covering several solar cycles) and the JPL TEC maps (from 1998 through 2009) were collected to investigate the equinoctial asymmetries in ionospheric electron density and its variation with solar activity. With solar activity increasing, the equinoctial asymmetry of noontime NmF2 increases at middle latitudes but decreases or changes little at low latitudes, while the equinoctial asymmetry of TEC increases at all latitudes. The latitudinal feature of the equinoctial asymmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 39 publications
(60 reference statements)
2
37
0
Order By: Relevance
“…For example, by Essex [] during solar high (2 years), by Titheridge and Buonsanto [] during solar high (3 years), by Zhao et al [] during solar high (6 years), by Chakraborty and Hajra [] during ascending solar phase (4 years), by L. Liu et al [] only during low solar (3 years), and by Chen et al [] during complete cycle 23 (11 years). As shown in Figure 1 of Chen et al [], the equinoctial asymmetry existed predominantly over all latitudes in low as well as high solar activity with peak of this asymmetry found near the crests of EIA and a decreasing trend elsewhere. In contrast to their results, our results evidently show (Figure d) an opposite equinoctial asymmetry over northern LL location during 2011–2013 (3 years) and over equator and southern LL locations only during 2011 of the current solar cycle 24.…”
Section: Resultsmentioning
confidence: 99%
“…For example, by Essex [] during solar high (2 years), by Titheridge and Buonsanto [] during solar high (3 years), by Zhao et al [] during solar high (6 years), by Chakraborty and Hajra [] during ascending solar phase (4 years), by L. Liu et al [] only during low solar (3 years), and by Chen et al [] during complete cycle 23 (11 years). As shown in Figure 1 of Chen et al [], the equinoctial asymmetry existed predominantly over all latitudes in low as well as high solar activity with peak of this asymmetry found near the crests of EIA and a decreasing trend elsewhere. In contrast to their results, our results evidently show (Figure d) an opposite equinoctial asymmetry over northern LL location during 2011–2013 (3 years) and over equator and southern LL locations only during 2011 of the current solar cycle 24.…”
Section: Resultsmentioning
confidence: 99%
“…By examining the sunset time during the two equinoxes, Liu et al (2015) reported that the mean sunset time during spring months is 25 min later than that in autumn months which led to the equinoctial scintillation onset time difference. It is relevant to mention that the phenomenon of equinoctial difference also exists in seasonal variation of ionospheric electron density at low and middle latitudes (Liu et al, 2010;Chen et al, 2012). Ren et al (2011Ren et al ( , 2012 suggested that the equinoctial asymmetry of equatorial vertical plasma drift plays an important role for the equinoctial difference of plasma density.…”
Section: Sf During Equinox Monthsmentioning
confidence: 99%
“…This period spanning over three years provides enough data for detecting the diurnal variations at the different seasons. In general, solar activity may be different between March equinox and September equinox of a year (Chen et al, 2012), thus the need to separate the equinox seasons. Figure 2 shows the distribution of the wind speeds within the selected latitude band.…”
Section: Methodology Data Sources and Selectionmentioning
confidence: 99%